An orange peel‐like nodule on the back: A case of Wells syndrome. Issue 7 (14th July 2022) - Baklouti, Massara; Sellami, Khadija; Triki, Meriam; Masmoudi, Abderrahman; Sellami, Tahya; Turki, Hamida
Abstract: Wells syndrome is a rare eosinophilic syndrome, associating inflammatory lesions, suggestive histological images and frequent eosinophilia. Wells syndrome is characterized by multiplicity of anatomoclinical forms. Clinically, lesions may be urticarial, annular, papulonodular, papulovesicular or bullous. On histopathology, the flame aspect is by no means specific and late. Abstract : Wells syndrome is a rare eosinophilic syndrome, associating inflammatory lesions, suggestive histological images, and frequent eosinophilia. The typical presentation is the plaque‐type variant. Wells syndrome is characterized by multiplicity of anatomoclinical forms. Lesions may be urticarial, annular, papulonodular, or bullous. On histopathology, the flame aspect is not specific and late.